Feline immunodeficiency virus: current insights into pathogenesis, clinical impact, and advances in treatment and vaccine development - Akhtar, Nahid; Mishra, Ragini; Tripathi, Shivakant; Redon-Marin, Santiago; Narsing Rao, Manik Prabhu; Cuspoca Orduz, Andrés Felipe; Leon Magdaleno, Jorge Samuel; Shaikh, Abdul Rajjak; Ruiz-Saenz, Julian; Cavallo, Luigi; Chawla, Mohit (Frontiers in Veterinary Science, 2025)
Feline immunodeficiency virus (FIV) is a retrovirus that infects both domestic and wild cats worldwide, causing a progressive decline in the immune function. FIV infection is a major concern for cat owners, particularly those with outdoor cats or multi-cat households, as it can lead to chronic illness and a reduced lifespan. The development of effective prevention and treatment strategies for FIV is therefore essential to improve the health and welfare of cats. This review article provides an overview of current knowledge on FIV, covering its epidemiology, prevalence, pathogenesis, risk factors, transmission, and management. It also discusses the various FIV subtypes, their geographical distribution, and their associations with different clinical outcomes. In addition, the review examines the clinical and pathophysiological features associated with FIV, including oral and respiratory infections, neurological disorders, renal diseases, and cancer. The review also discusses management strategies for FIV-infected cats, with a focus on advances in the development of antiretroviral drugs and immunomodulators. This review highlights the challenges of developing an effective FIV vaccine and provides a comprehensive summary of the latest advancements in FIV vaccine research. Additionally, it offers an overview of adjuvants used so far in FIV vaccine candidates and explores the potential application of adjuvants currently licensed for other vaccines. Overall, this review paper provides a comprehensive and up-to-date summary of current knowledge on FIV, highlighting key areas that require further research to improve treatment and prevention of this important feline viral infection.